2019
DOI: 10.1371/journal.pone.0220784
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between depression, health‑related behaviors, and internet addiction in female junior college students

Abstract: Introduction Depressive emotions can lead to subsequent unhealthy behaviors such as Internet addiction, especially in female adolescents; therefore, studies that examine the relationships among depression, health‑related behaviors, and Internet addiction in female adolescents are warranted. Purpose To examine (1) the relationship between depression and health-related behaviors and (2) the relationship between depression and Internet addiction. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 66 publications
(76 reference statements)
3
26
1
Order By: Relevance
“…Thus, interpersonal interactions on the Internet are on the increase [7]. Overuse of or addiction to the Internet may negatively influence teenagers' emotions [8]. Studies [8][9][10] have indicated that teenagers' Internet addiction is significantly correlated with depressed emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, interpersonal interactions on the Internet are on the increase [7]. Overuse of or addiction to the Internet may negatively influence teenagers' emotions [8]. Studies [8][9][10] have indicated that teenagers' Internet addiction is significantly correlated with depressed emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Overuse of or addiction to the Internet may negatively influence teenagers' emotions [8]. Studies [8][9][10] have indicated that teenagers' Internet addiction is significantly correlated with depressed emotions. However, few studies [8][9][10] discuss further the correlations between interpersonal interactions on the Internet and depressed emotions and whether the interpersonal interactions online actually influence teenagers' emotions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the negative correlation between solitude coping and severe depression revealed by this study means that improvement of individuals’ capacity for solitude can probably alleviate the negative influences of depression. In addition, in Taiwan, more than one-fourth of the national teenage population has experienced depressive moods (or insomnia), and the number of adolescents affected by these symptoms is increasing annually [ 45 , 46 , 47 ]. The enhancement of teenagers’ solitude capacity may be another way to improve the negative mood and/or sleep quality in these teenagers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, older people are more likely to achieve the recommended daily consumption of fruit and vegetables than young people [ 68 ]. Interestingly, the literature shows that young people with lower diet quality scores were more likely to report depressive symptoms [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%